Transnational ecological networks in Central Europe. A compilation of results and outputs from the EU Central Europe TransEcoNet Project. 2nd ed. - (:unkn) unknown (Rhombos, 2017)
Schutzgebiete wie Nationalparks oder Biosphärenreservate sind oft von weniger geschützten oder ungeschützten Bereichen umgeben. Häufig werden diese umliegenden Gebiete intensiv für Landwirtschaft, Verkehrsinfrastruktur, Industriestandorte und menschliche Siedlungen genutzt, was die Biodiversität beinträchtigen kann. Um die Artenvielfalt langfristig zu erhalten, müssen wertvolle Naturlandschaften durch ökologische Netzwerke räumlich miteinander verbunden werden. Die ländlichen Grenzregionen Mitteleuropas zeichnen sich besonders durch ein interessantes Mosaik von geschützten und nicht geschützten Gebieten aus, wobei die nicht geschützten Gebiete dennoch ökologisch wertvoll sein können. Mit der politischen und wirtschaftlichen Integration Europas sind diese ehemaligen abgelegenen Landschaften heute von raschen Veränderungen betroffen, und die Grenzgebiete stehen vor der Herausforderung, ein Gleichgewicht zwischen der wirtschaftlichen Entwicklung einerseits und dem Schutz ihres wertvollen Natur- und Kulturerbes andererseits zu finden.

In Central Europe protected areas, such as national parks or biosphere reserves, are often isolated patches of nature conservation. They are surrounded by less protected and/or unprotected areas. Frequently these surrounding areas are intensively used for agriculture, transport infrastructure, industrial sites and human settlements. To provide animals and plants with possibilities for migration, dispersal and forage and to conserve biodiversity in the long run, valuable natural landscapes need to be spatially connected by ecological networks. The idea of the project TransEcoNet (Transnational Ecological Networks in Central Europe) has been to analyse border areas in Central Europe regarding the spatial coherence of ecological networks, the status of biodiversity and ecosystem services and land use development past and present. In addition to spatio-ecological analyses socio-cultural topics such as awareness of ecological networks and general regional ecological values have also been considered. In this publication the individual chapters cover an inventory of ecological networks in Central Europe, an analysis of the history of these ecological networks, the assessment of their biodiversity and ecosystem services in selected regions as well as strategies for raising awareness for ecology as such and for ecological networks in particular. The articles within the chapters have varying spatial foci and also cover regional and local elements.
Keywords: Naturschutz; Landschaftsschutz; Naturschutzgebiet; Landschaftsökologie; Ökosystem; Raumnutzung; Nutzungskonflikt; Raumordnungspolitik; Grenzüberschreitende Zusammenarbeit; Biotopverbund; Vernetzung